Meeting Report: The Terabase Metagenomics Workshop and the Vision of an Earth Microbiome Project. Issue 3 (November 2010) - Gilbert, Jack; Meyer, Folker; Antonopoulos, Dion; Balaji, Pavan; Brown, C.; Brown, Christopher; Desai, Narayan; Eisen, Jonathan; Evers, Dirk; Field, Dawn; Feng, Wu; Huson, Daniel; et al.
Abstract Between July 18th and 24th 2010, 26 leading microbial ecology, computation, bioinformatics and statistics researchers came together in Snowbird, Utah (USA) to discuss the challenge of how to best characterize the microbial world using next-generation sequencing technologies. The meeting was entitled "Terabase Metagenomics" and was sponsored by the Institute for Computing in Science (ICiS) summer 2010 workshop program. The aim of the workshop was to explore the fundamental questions relating to microbial ecology that could be addressed using advances in sequencing potential. Technological advances in next-generation sequencing platforms such as the Illumina HiSeq 2000 can generate in excess of 250 billion base pairs of genetic information in 8 days. Thus, the generation of a trillion base pairs of genetic information is becoming a routine matter. The main outcome from this meeting was the birth of a concept and practical approach to exploring microbial life on earth, the Earth Microbiome Project (EMP). Here we briefly describe the highlights of this meeting and provide an overview of the EMP concept and how it can be applied to exploration of the microbiome of each ecosystem on this planet.